Examples of local histography against the policy of the Ottoman Empire in Algeria (Journal of Misan Researches, 2020)
Western mythology has exploited history in the context of ideological objectives of colonial and systemic proportions, based on the contempt of the other in its Western and transcendental theories. venerating the Western race and humiliating the Algerian Muslim race.  As a society that does not have historically and needs leaders, in response to historical Western mistakes, especially French ones. Cultural impulses have emerged in the form of perceptions, theses and opinions in three forms; politicized, purely scientific, and emotional, It took a teleological subject pertaining to the defense of the Algerian state before the French occupation. A counter-mythology emerged in the scientific arena for what Western mythology promoted while opposing the Ottoman period in Algeria. In this process, we present the following problematic;What are the orientations of their authors? Have they been able to refute Western mythological sophisms? What are the reasons for their hostility towards the Ottoman Empire? Was this mythology objective or a subjective ideology?